2016
DOI: 10.1007/s10336-016-1359-x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of migration in Common Redstarts (Phoenicurus phoenicurus) in relation to the vegetation phenology at residence sites

Abstract: Timing the annual cycle according to local conditions is crucial for animals in seasonal environments, because individual resource requirements must match seasonal resource availabilities. Pre-nuptial spring migration is especially time constrained in many migratory species, and thus tight adjustments of departure and arrival times to local environmental conditions can be expected. We determined non-breeding residences of Common Redstarts, an insectivorous Palearctic-African migrant, from a central European po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In agreement with previous studies 67 , 90 , we could not link between local vegetation phenology and departure timing of the redstart from the African non-breeding grounds. Given the large range of redstart on the African non-breeding ground, it is likely that we failed to detect such a trend due to the insufficient range accuracy for the populations flying through Israel.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous studies 67 , 90 , we could not link between local vegetation phenology and departure timing of the redstart from the African non-breeding grounds. Given the large range of redstart on the African non-breeding ground, it is likely that we failed to detect such a trend due to the insufficient range accuracy for the populations flying through Israel.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Newson, et al 86 present earlier arrival of redstart to breeding grounds in the UK between 2002–2011 than in the mid-1960s, and Porkert et al 62 demonstrated advanced egg-laying dates in nine Eurasian populations of the redstart. The advanced arrival of both sexes at the breeding ground, in contrast to the trend found only in males in Israel, may be a result of females adjusting migration speed en route 5 , 67 , 87 . Sexual differences in changes to migration timing were also shown in willow warbler Phylloscopus trochilus in Sweden, where males advanced arrival more strongly than females 84 .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Such strategies could occur in several of the longest-distance migrating species wintering south of the equator, for example, marsh warblers ( Acrocephalus palustris ) ( 23 ), but are potentially more constrained in species wintering further north in, for example, West Africa, where resources generally decline from early fall ( 53 , 54 ). The species we tracked showed no consistent pattern in, whether birds experienced increasing or decreasing greenness.…”
Section: Discussionmentioning
confidence: 99%